The Essence of the Educational Process and its Society Place in Development (Journal of Pedagogical Inventions and Practices, 2023)
Education is one of the main categories of pedagogy, it is aimed at introducing a person to social experiences in all its forms - knowledge, emotions, aesthetics, rules of etiquette and developing the individual's internal characteristics, opportunities and abilities, is an activity. The theory of education is based on the rich experience of Eastern thinkers and folk pedagogy. The theory of education uses the knowledge of such sciences as philosophy, sociology, ethics, aesthetics, physiology, psychology to justify its rules. The theory of education is inextricably linked with other departments of pedagogy: that is, the general foundations of pedagogy, the theory of education and the management of the public education system.